Prognostic factors for survival in advanced thymomas: The role of the number of involved structures. Issue 5 (12th July 2021) - Chiappetta, Marco; Aprile, Vittorio; Lococo, Filippo; Zanfrini, Edoardo; Nachira, Dania; Meacci, Elisa; Korasidis, Stylianos; Ambrogi, Marcello; Lucchi, Marco; Margaritora, Stefano
Abstract: Background and Objectives: The Masoka‐Koga and tumor node metastases staging systems for thymoma are based on structures involved, but the prognostic role of the number of infiltrated/involved structures is still debated. We analyzed the prognostic role of involved structures and their combinations in locally advanced thymomas patients. Methods: Data on 174 surgically treated locally advanced thymoma patients from 1/01/1990 to 31/12/2015 were reviewed. Clinical and pathological characteristic, involved structures, number of involved structures and different combinations were correlated to cancer specific survival (CSS) using Kaplan–Meier product‐limit method. Results: Five and 10‐year CSS was 92% and 87%. Masaoka Stage 3 ( p < 0.001), absence of pericardial involvement ( p = 0.001), number of involved structures ( p = 0.018), R0 ( p < 0.001) and adjuvant radiotherapy ( p = 0.008) were favorable prognostic CSS factors. A significant better prognosis was present in ≤2 involved structures vs >2 involved structures (5‐ and 10‐year CSS: 95% and 93% vs. 80% and 51%). Multivariable analysis confirmed as independent prognostic factor R0 ( p = 0.033, hazard ratio [HR]: 0.093, 95% confidence interval [CI] 0.010–0.827) and number of involved structures ( p = 0.046, HR: 0.187, 95% CI: 0.036–0.968). In Masaoka Stage 3, patients with ≤2 involved structures had a significant better CSS than patients with >2 (10‐year CSS: 98% vs. 73%, p = 0.008). Conclusions: The number of involved structures and the concomitant involvement of the pericardium seems to be associated with a poor prognosis in surgically treated advanced thymoma patients.